Vasopressin increases water permeability of kidney collecting duct by inducing translocation of aquaporin-CD water channels to plasma membrane. - Nielsen, S (1995)
Water excretion by the kidney is regulated by the peptide hormone vasopressin. Vasopressin increases the water permeability of the renal collecting duct cells, allowing more water to be reabsorbed from collecting duct urine to blood. Despite long-standing interest in this process, the mechanism of the water permeability increase has remained undetermined. Recently, a molecular water channel (AQP-CD) has been cloned whose expression appears to be limited to the collecting duct. Previously, we immunolocalized this water channel to the apical plasma membrane (APM) and to intracellular vesicles (IVs) of collecting duct cells. Here, we test the hypothesis that vasopressin increases cellular water permeability by inducing exocytosis of AQP-CD-laden vesicles, transferring water channels from IVs to APM. Rat collecting ducts were perfused in vitro to determine water permeability and subcellular distribution of AQP-CD in the same tubules. The collecting ducts were fixed for immunoelectron microscopy before, during, and after exposure to vasopressin. Vasopressin exposure induced increases in water permeability and the absolute labeling density of AQP-CD in the APM. In parallel, the APM:IV labeling ratio increased. Furthermore, in response to vasopressin withdrawal, AQP-CD labeling density in the APM and the APM:IV labeling ratio decreased in parallel to a measured decrease in osmotic water permeability. We conclude that vasopressin increases the water permeability of collecting duct cells by inducing a reversible translocation of AQP-CD water channels from IVs to the APM.